Autonomous Shadowing Practice and Prosodic Development in Intermediate Learners of Japanese: A Mixed-Methods Study - Jiaan Xu (Chi e Journal of Japanese Learning and Teaching, 2026)
Autonomous oral practice is widely encouraged in Japanese language learning, but its pronunciation benefits are not always explained in ways that link measurable speech change with native-speaker perception. This mixed-methods study examined how repeated shadowing practice supported prosodic development in three intermediate learners of Japanese. Over seven weeks, participants completed two shadowing sessions per week using textbook audio recordings as model input. The analysis combined two approaches: acoustic inspection of fundamental frequency (FO) contours and timing patterns using PRAAT, and perceptual evaluation by two native Japanese speakers focusing on accent, intonation, word rhythm and overall improvement. Across learners, second attempts on the same material generally showed smoother pitch movement, more stable rhythmic organization, and higher perceptual ratings. Indicating improvement in prosodic naturalness even within a short practice cycle. At the same time, development was not uniform. Some learners improved mainly through more coherent intonation, while others showed faster delivery that sometimes coincided with reduced segmental precision, such as shortened long vowels. These findings suggest that autonomous shadowing can effectively support prosodic development, while also highlighting the need for pacing and feedback to maintain accuracy as fluency increases.